Pertumbuhan semai cendana (Santalum album Linn.) pada beberapa ukuran kantung plastik di daerah semiarid - I Komang Surata (Foresty Faculty of Hasanuddin University, 2012)
Mortality of sandalwood plantings in the semiarid region is high (less than 50 %), due to poor quality. One of seedling of the alternatives to reduce this mortality is using optimal container size. The method is hoped to increase the growth and survival rate of sandalwood seedlings in the field. The objective of this study was to determine the effects of various sizes of seedling container on growth and to recommend the best polybag size for sandalwood nursery. The study was conducted in Complete Randomized Design method using container size of polybag (wide x length as main treatment) i.e.: 7 x 20 cm2, 8 x 20 cm2, 9 x 20 cm, 10 x 21 cm2, 11 x 22 cm2, 12 x 23 cm2, 13 x 23 cm2, 14 x 24 cm2, and 15 x 252 cm. Experiment consisted of 30 replications. The polybag was filled with the potting medium consisting soil, sand, and compost in volume ratio of 4:1:1 and sown with Alternanthera sp. as a primary host plant in all treatment. The results of the experiment proved that application of polybag size (7 cm x20 cm to 15 cm x 25 cm) had significant effects on height, diameter, dry weight total, top root ratio, quality index and survival of sandalwood seedling at six months old. The application of polybag size 15 x 25 cm2 (1080 mL) produced the best growth i.e. height (24.53 cm ), diameter (4.27 mm), dry weight total (1.86 g), top root ratio (0.54), quality index (0.28) and survival (92 %).